2008
DOI: 10.1096/fj.08-108985
|View full text |Cite
|
Sign up to set email alerts
|

Combinatorial patterns of somatic gene mutations in cancer

Abstract: Cancer is a complex process in which the abnormalities of many genes appear to be involved. The combinatorial patterns of gene mutations may reveal the functional relations between genes and pathways in tumorigenesis as well as identify targets for treatment. We examined the patterns of somatic mutations of cancers from Catalog of Somatic Mutations in Cancer (COSMIC), a large-scale database curated by the Wellcome Trust Sanger Institute. The frequently mutated genes are well-known oncogenes and tumor suppresso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
257
0
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 257 publications
(267 citation statements)
references
References 46 publications
7
257
0
3
Order By: Relevance
“…Clinical evidence is compelling for histologic progression of breast cancer through atypical hyperplasia, ductal carcinoma in situ (DCIS), invasive ductal carcinoma, and metastatic stages. 1 Such histopathologic progression studies and mutational profiling of epithelial cancers 2,3 suggest that acquisition of invasive potential is a relatively late event. However, genomic data analyses have revealed that most tumor cell gene expression changes occur at the transition from normal to DCIS, with few additional changes in expression occurring at the transition from DCIS to overt invasive disease.…”
mentioning
confidence: 99%
“…Clinical evidence is compelling for histologic progression of breast cancer through atypical hyperplasia, ductal carcinoma in situ (DCIS), invasive ductal carcinoma, and metastatic stages. 1 Such histopathologic progression studies and mutational profiling of epithelial cancers 2,3 suggest that acquisition of invasive potential is a relatively late event. However, genomic data analyses have revealed that most tumor cell gene expression changes occur at the transition from normal to DCIS, with few additional changes in expression occurring at the transition from DCIS to overt invasive disease.…”
mentioning
confidence: 99%
“…In the same way, the existence of mutually exclusive mutations in the same tumor type highlights the importance of differentiate subgroups. These observations reveal the importance of identify the tumor specific genetic pattern (Yeang et al, 2008).…”
Section: Molecular Events Produced In a Rectal Cancermentioning
confidence: 86%
“…As we have seen this mutagenic mechanism remains in the tumor after cancer treatment. Yeang et al (2008) detected significant different mutational patterns between cell lines and tumor samples. The effect of a polymorphism or somatic mutation in a protein is firstly tested in a cell line.…”
Section: T0mentioning
confidence: 92%
“…BRAF has been discovered to be the most commonly mutated oncogene in melanoma (50-60%) (Davies, Bignell et al 2002), papillary thyroid carcinoma (36-53%) (Yeang , McCormick et al 2008), colon carcinoma (57%), serous ovarian carcinoma (~30%) (Yeang , McCormick et al 2008), and hairy cell leukemia (100%) (Tiacci, Trifonov et al 2011). To date, >60 distinct mutations in the BRAF gene have been identified (Table 1) (Garnett and Marais 2004;Catalog of Somatic Mutations in Cancer: www.sanger.ac.uk/genetics/CGP/cosmic/).…”
Section: Activating Mutations At Brafmentioning
confidence: 99%